Allele-specific repression of lymphotoxin-alpha by activated B cell factor-1. - Knight, J; Keating, B; Kwiatkowski, D (2004)
Genetic variation at the human LTA locus, encoding lymphotoxin-alpha, is associated with susceptibility to myocardial infarction, asthma and other diseases. By detailed haplotypic analysis of the locus, we identified a single-nucleotide polymorphism (SNP) at LTA+80 as a main predictor of LTA protein production by human B cells. We found that activated B-cell factor-1 (ABF-1) binds to this site in vitro and suppresses reporter gene expression, but only in the presence of the LTA+80A allele. Using haplotype-specific chromatin immunoprecipitation, we confirmed that ABF-1 is preferentially recruited to the low-producer allele in vivo. These findings provide a molecular model of how LTA expression may be genetically regulated by allele-specific recruitment of the transcriptional repressor ABF-1.